UPAYA PENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPS MELALUI METODE FEEDBACK PARTNER (UMPAN BALIK) PADA SISWA KELAS IV SDN 18 BATANG GASAN - Kartina Kartina (STKIP Pesisir Selatan, 2019)
Based on the learning outcomes of Class IV students at SDN 18 Batang Gasan in social studies subjects it was found that student learning outcomes in social studies subjects were still very low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in sub-social studies subjects. Explain the relationship between structure, function, and processes and disorders / diseases that can occur in the excretion system in humans and animals (fish and insects) through the method Feedback Partner in Class IV SDN 18 Batang Gasan. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subjects of the study consisted of 30 students of Class IV SDN 18 Batang Gasan. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the Feedback Partner Method (Feedback) can improve student learning outcomes in sub-social studies subjects Explain the relationship between structure, function, and processes and disorders / diseases that can occur in the excretory system in humans and animals (fish and insects) at SDN 18 Batang Gasan. Student learning outcomes from cycle I to cycle II. The learning outcomes of students in the first cycle were 55.33 (Enough), increasing to 84.43 (Good) with an increase of 29.10%.